Sentiment Analysis Ulasan Pengguna Aplikasi Pada PT. XYZ Dalam Bidang Farmasi Menggunakan Algoritma Naïve Bayes Classifier - Tia Arlin Dita (2022)
Information technology has had a positive impact on people's lives. The application of applications in a company is a necessity that cannot be avoided. PT. XYZ, which is engaged in pharmaceuticals, is a pharmaceutical industry company in Indonesia that has implemented an application that runs on the Google Play Store. Applications on the Google Play Store can be accessed widely by the public. To determine public acceptance of the application, it is necessary to analyze public opinion on the application. Application user reviews on the Google Play Store can be used to explore public opinion information. In this study, classification will be carried out using the nave Bayes method to find out public opinion on the application of PT. XYZ which is engaged in pharmacy. The stage in conducting this Sentiment Analysis is to collect reviews that will be carried out Pre-Processing after that the classification is carried out using the Nave Bayes method. The results of this study obtained that the review data obtained were 900 consisting of 450 positive data and 450 negative data. The results obtained from the classification process using the naive bayes classifier algorithm with the distribution of training data by 80% and 20% test data get good results. These results are shown by an evaluation test using a confusion matrix so that an accuracy value of 90% is obtained.